Chigger mites (Acariformes: Trombiculidae) of Israel. Issue 3 (3rd April 2022) - Stekolnikov, Alexandr A.; Mumcuoglu, Kosta Y.
ABSTRACT: The chigger mites of Israel were reviewed based on the examination of museum collections, one new sample, and literature data. At present, seven species of chiggers are known from this country. Kepkatrombicula acomys (Radford, 1957) comb. n . was re-described based on a paratype. Neotrombicula tadjikistanica Kudryashova and Abou-Taka, 1987, the type species of Kepkatrombicula Kudryashova and Stekolnikov 2010, is synonymized with K. acomys. Neotrombicula autumnalis (Shaw, 1790) was recorded in Israel for the first time based on a sample collected from a cat. The original material of Miyatrombicula cwilichi Cwilich, Hadani, Peled and Shimshoni, 1965 ( nomen nudum ) was examined in a museum collection; this species was found to be identical with Neotrombicula heptneri Kudryashova, 1973; the latter was recorded in Israel for the first time based on a sample from a goat. The diagnosis of Neotrombicula palestinensis (Radford, 1957) was corrected based on our examination of two paratypes and one additional specimen. The status of type specimens of Pentidionis agamae (André, 1929) was clarified based on our examination of the type series